PRONUNCIATION ERRORS ANALYSIS UTTERED BY THE TEENAGER IN PANYABUNGAN - Rahmat Huda; Annisah Fitri Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2021)
This research was conducted based on the phenomenon that happened in society. The teenager hasa low ability in pronunciation. They got difficulty pronouncing English words including diphthong sounds. This research was conducted based on qualitative trustworthiness analysis. And to help the analysis of the data the researcher used the Spying Method. In collecting the data, the researcher made some interviews and oral tests usingthe method by the teenagers to pronounce some words including diphthong sound while the researcher recorded them. Then, the researcher made the transcription of their recording to be analyzed of their errors in pronouncing diphthong sounds. The result showed that teenagers made six mistakes in the center and made four mistakes in closing. That sound made error by teenagers are ÉªÉ™,aÉª,É”Éª, É™ÊŠ, eÉ™, ÊŠÉ™that is sound of diphthong that error made by teenager problem.